Validation of the Chinese version of the Clinical Assessment Interview for Negative Symptoms (CAINS): a preliminary report - Chan, Raymond C. K.; Shi, Chuan; Lui, Simon S. Y.; Ho, Karen K. Y.; Hung, Karen S. Y.; Lam, Joanna W. S.; Wang, Ya; Cheung, Eric F. C.; Yu, Xin (Frontiers in Psychology, 2015)
The present study aimed to examine the psychometric properties of the Chinese version of the Clinical Assessment Interview for Negative Symptoms (CAINS). We recruited 68 patients with schizophrenia from the Chinese setting. The findings showed a generally consistent two-factor structure with the original version, namely “expression” and “motivation-pleasure”. There is a minor cultural variation in perceiving these items in the Chinese culture. However, the present study demonstrated that the Chinese version of the CAINS appears to be a valid and reliable clinical tool for the assessment of negative symptoms in the Chinese setting.